A stubborn nasogastric tube: self-knotting of a nasogastric tube. Issue 7 (23rd July 2022) - Tsandiraki, Justin; Tendai, Joylene; Likiliwike, Arnold D; Moirana, Ezekiel N; Msuya, David; Tarmohamed, Murad
Abstract: Nasogastric tubes (NGT) are widely used and generally harmless as such, complications are uncommon. NGT knotting is one such complication. We report a 45-month-old female with spontaneously knotted NGT that was identified and safely removed without complications. NGT knotting detection needs a high index of suspicion; if not detected and managed in a proper way, it may lead to severe complications. We discuss this case to raise awareness of this complication and how to minimize the likelihood of it happening and improve patient outcome.